2003
DOI: 10.1021/ie030333f
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ultrasound on Adsorption and Desorption Processes

Abstract: The following paper is aimed at finding the effects of ultrasound on adsorption/desorption processes. Experiments concerning the ultrasonic power input indicate that particles absorb ultrasonic energy effectively if they are in resonance with the ultrasound. The ultrasonic energy is dissipated into heat. Hence, desorption processes are promoted. Desorption experiments at different frequencies show that neither particle oscillations nor cavitation effects are responsible for ultrasonically enhanced desorption p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(42 citation statements)
references
References 19 publications
1
40
0
1
Order By: Relevance
“…The effects of ultrasounds on the adsorption and desorption of phenolics has been reported (Schneller and Yang, 2001;Li et al, 2002b;Breitbach et al, 2003). Upon sonication, attrition of ACs should be avoided by controlling frequency and intensity, whereas polymeric resins can withstand cavitational effects (Rege et al, 1998).…”
Section: Microwave Heatingmentioning
confidence: 99%
“…The effects of ultrasounds on the adsorption and desorption of phenolics has been reported (Schneller and Yang, 2001;Li et al, 2002b;Breitbach et al, 2003). Upon sonication, attrition of ACs should be avoided by controlling frequency and intensity, whereas polymeric resins can withstand cavitational effects (Rege et al, 1998).…”
Section: Microwave Heatingmentioning
confidence: 99%
“…In recent years the research regarding the application of ultrasounds in hydrometallurgy, in dissolution operations [24][25][26][27][28][29][30][31][32][33][34][35][36][37], ionic exchange [38][39][40][41][42][43][44][45][46][47], and solvent extraction [48][49][50][51][52][53] has expanded.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the destruction o f organic com pounds such as long-chain hydrocarbons was resulted from the production o f hydroxyl radicals (Feng and A ldrich, 2000). This usually occurs when the ultrasound is in the mid frequency from 200 to 400 kH z (Breitbach et al, 2003;Petrier and Francony, 1997). In this study, the condition for the production o f hydroxyl radicals was not reached at low frequency o f 20 kHz, thus there w as no significant destruction to change the PHC proportions in the recovered oil.…”
Section: Effects Of Salt Addition (Sodium Chloride)mentioning
confidence: 58%
“…(Feng and Aldrich, 2000;M ason and Lorimer, 2002). It has been reported that the phenom ena o f ultrasonic cavitation could play a significant role in enhancing the desorption o f adsorbed molecules, and the effect o f cavitation depends on the size o f bubbles while m ore energy could be stored w ithin the bigger bubbles (Breitbach et al, 2003). In this study, the low frequency o f ultrasound (20 kH z) was applied.…”
Section: Com Parison O F Methodsmentioning
confidence: 99%
See 1 more Smart Citation